Licofelone Attenuates LPS-induced Depressive-like Behavior in Mice: A Possible Role for Nitric Oxide - Seyyedeh Elaheh Mousavi; Pegah Saberi; Naeemeh Ghasemkhani; Nahid Fakhraei; Rezvan Mokhtari; Ahmad Reza Dehpour (Frontiers Media S.A., 2018)
PURPOSE: Licofelone, a dual cyclooxygenase/5-lipoxygenase inhibitor, possesses antioxidant, antiapoptotic, neuroprotective, and anti-inflammatory properties. The aim of the present study was to investigate the effect of licofelone on lipopolysaccharide (LPS)-induced depression in a mouse model and also a possible role for nitric oxide (NO). METHODS: To elucidate the role of NO on this effect of licofelone (5 and 20 mg/kg, i.p.), L-NAME, a non-specific NO synthase (NOS) inhibitor; aminoguanidine (AG), a specific inducible NOS (iNOS) inhibitor; 7-nitroindazole (7-NI) a preferential neuronal NOS inhibitor (nNOS) and; L-arginine (L-Arg), as a NO donor, were used. The animal's behaviors were evaluated employing forced swimming test (FST), tail suspension test (TST) and open field test (OFT). RESULTS: LPS (0.83 mg/kg, i.p.) induced depressive-like behavior increasing immobility time in FST and TST. Conversely, licofelone (20 mg/kg i.p.) reversed the depressive effect of LPS and lowered the immobility time in FST and TST. On the other hand, pretreatment with L-Arg also reversed the antidepressant-like effect of licofelone (20 mg/kg) in FST and TST. On the other hand, L-NAME (10 and 30 mg/kg), AG (50 and 100 mg/kg) and 7-NI (60 mg/kg) could potentiate licofelone (5 mg/kg) and lowered the immobility duration. CONCLUSIONS: NO down-regulation possibly through iNOS and nNOS inhibition may involve in the antidepressant property of licofelone.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.